Spontaneous Tumor Lysis Syndrome - Alicia C. Weeks MD; Michelle E. Kimple PhD (SAGE Publishing, 2015)
Tumor lysis syndrome (TLS) is a known complication of malignancy and its treatment. The incidence varies on malignancy type, but is most common with hematologic neoplasms during cytotoxic treatment. Spontaneous TLS is thought to be rare. This case study is of a 62-year-old female admitted with multisystem organ failure, with subsequent diagnosis of aggressive B cell lymphoma. On admission, laboratory abnormalities included renal failure, elevated uric acid (20.7 mg/dL), and 3+ amorphous urates on urinalysis. Oliguric renal failure persisted despite aggressive hydration and diuretic use, requiring initiation of hemodialysis prior to chemotherapy. Antihyperuricemic therapy and hemodialysis were used to resolve hyperuricemia. However, due to multisystem organ dysfunction syndrome with extremely poor prognosis, the patient ultimately expired in the setting of a terminal ventilator wean. Although our patient did not meet current TLS criteria, she required hemodialysis due to uric acid nephropathy, a complication of TLS. This poses the clinical question of whether adequate diagnostic criteria exist for spontaneous TLS and if the lack of currently accepted guidelines has resulted in the underestimation of its incidence. Allopurinol and rasburicase are commonly used for prevention and treatment of TLS. Although both drugs decrease uric acid levels, allopurinol mechanistically prevents formation of the substrate rasburicase acts to solubilize. These drugs were administered together in our patient, although no established guidelines recommend combined use. This raises the clinical question of whether combined therapy is truly beneficial or, conversely, detrimental to patient outcomes.